Hydrogel-based triboelectric nanogenerators: Properties, performance, and applications - Torres, F.G.; Troncoso, O.P.; De-la-Torre, G.E. (John Wiley and Sons, 2022)
The development of triboelectric nanogenerators (TENGs) in 2012 revolutionized the vision of environmental energy harvesting. Nowadays, TENG assembly, working mode, and material selection are investigated continuously in order to obtain high-performance and long-lasting devices. Hydrogels are flexible and stretchable water-swollen 3D polymer networks, which can be tailored to conduct electricity and render outstanding mechanical properties. Hydrogels have been used to develop novel flexible wearable TENGs. Here, we review the current knowledge concerning hydrogel-based TENGs, including an overview of relevant hydrogel characteristics, hydrogel-based TENG performance, and their practical applications. The single-electrode TENG working mode is the most popular in hydrogel-based TENGs as they can be easily attached and stretched for biomechanical energy harvesting. Hydrogel-based TENGs have demonstrated to be capable of delivering high electrical output (250-400 V, ≥10 μA) and being robust enough for devices that last for several months. Biomechanical energy sensing and harvesting, smart farming, biomedical, and human–machine control interfaces are investigated as potential applications of hydrogel-based TENGs. Interestingly, energy harvesting from human motion is of particular interest for this type of TENG due to its outstanding stretchability, strength, and additional physical properties, such as self-healing ability. In most cases, the devices are capable of powering small electronics entirely from harvested biomechanical energy. Biomedical applications involved wound healing acceleration driven by TENG-powered electrical stimuli and disease monitoring, including implantable devices. Despite showing promising electrical performance, controlling water evaporation is still challenging to maintain the mechanical and conductive properties of hydrogel-based TENGs. On the other hand, fully biodegradable TENGs are largely unexplored, as well as many applications, such as blue energy harvesting, the internet of things, and others. The next steps in this line of research must focus on addressing the main challenges of hydrogel-based TENGs and filling the application knowledge gaps.
Keywords: Triboelectric effect; Energy harvesting; Self-healing hydrogels; Wearable technology; Electronics; Wearable computer; Materials science; Nanotechnology; Mechanical energy; Electrical engineering; Computer science; Engineering; Energy (signal processing); Power (physics); https://purl.org/pe-repo/ocde/ford#2.05.01